Transglutaminase-mediated crosslinking of a host defence peptide derived from human apolipoprotein B and its effect on the peptide antimicrobial activity - Dell'Olmo, Eliana; Gaglione, Rosa; Arciello, Angela; Piccoli, Renata; Cafaro, Valeria; Di Maro, Antimo; Ragucci, Sara; Porta, Raffaele; Giosafatto, C. Valeria L. (Biochimica et biophysica acta. General subjects, 2021)
Background Microbial transglutaminase (mTG) has been successfully used to produce site-specific protein conjugates derivatized at the level of Gln and/or Lys residues for different biotechnological applications. Here, a recombinant peptide identified in human apolipoprotein B sequence, named r(P)ApoBL and endowed with antimicrobial activity, was studied as a possible acyl acceptor substrate of mTG with at least one of the six Lys residues present in its sequence. Methods The enzymatic crosslinking reaction was performed in vitro using N,N-dimethylcasein, substance P and bitter vetch (Vicia ervilia) seed proteins, well known acyl donor substrates in mTG-catalyzed reactions. Mass spectrometry analyses were performed for identifying the Lys residue(s) involved in the crosslinking reaction. Finally, bitter vetch protein-based antimicrobial films grafted with r(P)ApoBL were prepared and, their biological activity evaluated. Results r(P)ApoBL was able to be enzymatically modified by mTG. In particular, it was demonstrated the highly selective crosslinking of the peptide under study by mTG at level of Lys-18. Interestingly, the biological activity of the peptide when grafted into protein-based films was found to be lost following mTG-catalyzed crosslinking. Conclusions r(P)ApoBL was shown to be an effective acyl acceptor substrate of mTG. The involvement of Lys-18 in the enzymatic reaction was demonstrated. In addition, films grafted with r(P)ApoBL in the presence of mTG lost antimicrobial property. General significance A possible role of mTG as biotechnological tool to modulate the r(P)ApoBL antimicrobial activity was hypothesized, and a potential use in food packaging of protein-based films grafted with r(P)ApoBL was suggested. •r(P)ApoBL was shown to be an effective acyl acceptor substrate of mTG.•The involvement of (P)ApoBL Lys-18 in the enzymatic reaction was demonstrated.•Bitter vetch protein-based antimicrobial films grafted with (P)ApoBL were prepared.•Films grafted with (P)ApoBL in the presence of mTG lost antimicrobial property.